Abstraction, Concrescence, and Identity in Descriptive Metadata. Issue 1 (2nd January 2018) - Radio, Erik
ABSTRACT: Descriptive metadata is affected by the challenge of using language that is resilient to semantic transformation over time. Yet, part of this is directly related to a bibliographic rift between abstract and concrete elements. By exploring the materiality of information objects and how descriptive values are subsequently derived, ideological formations and their impact become apparent. An examination of the origins of abstract elements demonstrates their identitarian tendencies and the effect on conceptual organization. Alternatives offered by negative dialectics and critical realism are explored toward a different model of information organization and retrieval.